Pengaruh Sosio Budaya dalam Pemberian ASI Eksklusif dan MP-ASI Dini Dikaitkan dengan Status Gizi pada Anak Usia 6-23 Bulan di Wilayah Kerja Puskesmas Banyuanyar Kabupaten Sampang - Anna Mahsusoh; Adelia Perwita Sari; Ira Nurmala; Oedojo Soedirham (Media Gizi Kesmas, 2024)
Introduction: Substance abuse is a global public health problem that is increasingly being used by young people. Republic of Indonesia Constitution No. 35 Year 2009 mandates all drug users to get rehabilitation service access. Yayasan PLATO use Addiction Severity Index (ASI) instruments in the rehabilitation process of substance addiction. This study aimed to analyze ASI Instruments as a progress of recovering addict joined rehabilitation. Method: The research design of this study used cross-sectional approach, with the sample was total population of 69 respondents. The study used secondary data taken from Rehabilitation Annual report of IPWL Yayasan PLATO 2021. Data of ASI assessment were analyzed using Wilcoxon Signed Ranks Test and The statistical significance was set at p< 0.05. Results: The study showed that 6 domains of ASI namely medical status, work/support, substance use, legal status, family/social and psychiatric status have P value <0.05. There were significant differences before and after rehabilitation treatment, Conclusion:  Drug users joining recovery treatment at Yayasan PLATO had a good progress, problems in each domain based on ASI instruments had decrease. Family support and social environment support is needed to maintain the recovery process and prevent from relapse.